Communication Competence of Teachers of Al-Qur'an Education Centers in the Teaching and Learning Process in Padang City - Putri, Syafni Nolla; Arif, Ernita; Sarmiati, Sarmiati (Hikmah, 2024)
This study aims to analyze the communication competence of teachers in Islamic religious education institutions, especially in the Al-Quran Education Center in Padang City. This research uses qualitative research method with case study approach and constructivism framework, this research explores communication competence among teachers of Qur’anic education center  in Jannatul Mukmin. Data collection was conducted using observation, interview, and documentation study techniques. Data analysis used data collection techniques, data reduction, data presentation and conclusion drawing. The results revealed that the Padang City government, through the Education and Culture Office, improved the communication competence of Qur’anic education center  teachers by conducting special training on communication skills, namely public speaking, active listening skills, and classroom management), mentoring programs from senior teachers, the establishment of regular discussion forums, the use of educational technology such as instructional videos, interactive applications, and e-learning platforms. The implications of this research can be used as a guide for Islamic religious education institutions in improving teachers' communication competencies and the overall quality of religious education.